Tinjauan Yuridis Perjanjian Kerja tentang Hubungan Kerja Flexible Work (Studi Komparasi Antara Indonesia dan Inggris) - Khomarudin Gilang Ramadhan; Arief Rachman Hakim (Jurnal Hukum Lex Generalis, 2025)
This research discusses the comparison of the form of flexible work agreement between Indonesia and the UK in the perspective of labor law. Flexible work is a work arrangement that provides flexibility in determining the time and location of work to create a balance between work and personal life. In Indonesia, flexible work agreements have not been comprehensively regulated in labor regulations, causing legal uncertainty for workers. In contrast, the UK has established a clear legal framework through the Employment Rights Act 1996 and Flexible Working Regulations 2014 that provides stronger protection to workers. This difference in regulatory approach indicates the need for labor law reform in Indonesia to provide justice for flexible work workers. This research aims to analyze the form of flexible work agreements and the level of legal protection received by workers in both countries.